Utilization of Media and Technology in Learning Islamic Religious Education - Amrullah, Hilman Ihza; Alif Nur Fathlii Amarta; Taufik Qurhahman; Amali (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research explores the use of media and technology in learning Islamic Religious Education in the digital era. The application of modern technology and interactive media has the potential to improve the quality and effectiveness of the PAI learning process. This study will analyze various technological platforms and tools used to deliver PAI material to students. Digital media such as learning videos, mobile applications and e-learning platforms can help improve students' understanding of PAI material. Apart from that, the use of technology also facilitates more interactive and interesting learning, and supports independent learning. This study also emphasizes the importance of educators' readiness to integrate technology into the PAI curriculum and the need for training and support for teachers. Proper use of technological media will bring positive changes in Islamic Religious Education learning